IMAGENS ARQUETÍPICAS NA RELAÇÃO PROFESSOR-ALUNO NA ESCOLA: em busca de um encantamento no processo ensino-aprendizagem - Brussio, Josenildo Campos (2008)
Approach the relationship between teacher and student in the hall-of-classroom by the Theory of Imaginary, aiming to seize the archetypal images that permeate the relationship between students and teachers in the teaching-learning process. As theoretical reference and methodological tools, we expect isotopic classification of images of Gilbert Durand (1997), the poetic of dreams and poetic of the area of Gaston Bachelard (2006/1998) and the concept of archetypes of Carl Jung (1996). Still use the design freedom and the narrative, in addition to the questionnaire open and the observation of the field for the capture of images. Thus, we reviewed them and found that if organized into three main areas: 1 - images for the school, 2 - images for the teacher and 3 - images for the student. Also noticed that the images suggested a possible enchantment exist in the relationship between teachers and students in the teaching-learning process.